Chernoff bound and saddlepoint approximation for outage probability in IRS-assisted wireless systems - Wang, T; Chen, G; Coon, JP; Badiu, M-A (IEEE, 2022)
We analyze the outage probability of an intelligent reflecting surface (IRS)-assisted communication network. An upper bound on the outage probability is formulated based on the Chernoff inequality. Furthermore, through an exact asymptotic (a large number of reflecting elements) analysis based on a saddlepoint approximation, we derive closed-form expressions of the outage probability for systems with and without a direct link and obtain the corresponding diversity orders. Simulation results corroborate our theoretical analysis and show the inaccuracies inherent in using the central limit theorem (CLT) to analyze system performance. Our analysis is accurate even for a small number of IRS elements in the high signal-to-noise ratio (SNR) regime.